2021
DOI: 10.1108/jd-10-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

A thematic analysis of library association policies on services to persons with disabilities

Abstract: PurposeLibrary association policies and guidelines are important to study because they reflect consensus values of the profession. As such, they can shape the association, itself, and set the tone for the values of its individual members in their professional practice. From the titles alone, these documents proclaim themselves to be guides for the development of individual library policy. Additionally, as library and information science (LIS) graduate education programs are accredited by national associations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In a wider setting, LIS education being informed by professional association policy (Hill, 2021), Blackburn (2015) recommends the inclusion of cultural competence as a key component of professional guidelines, LIS curriculum and practice, thus building on the ‘virtuous circle’ (Jaeger and Franklin, 2017; Jaeger et al, 2015) which fosters inclusion throughout the professional development and practice cycle. This is also highlighted by Caidi and Dali (2015) who recommend a holistic approach whereby LIS schools should consider the influence of their marketing and student recruitment on developing more diverse culture.…”
Section: Nine Repertoiresmentioning
confidence: 99%
See 2 more Smart Citations
“…In a wider setting, LIS education being informed by professional association policy (Hill, 2021), Blackburn (2015) recommends the inclusion of cultural competence as a key component of professional guidelines, LIS curriculum and practice, thus building on the ‘virtuous circle’ (Jaeger and Franklin, 2017; Jaeger et al, 2015) which fosters inclusion throughout the professional development and practice cycle. This is also highlighted by Caidi and Dali (2015) who recommend a holistic approach whereby LIS schools should consider the influence of their marketing and student recruitment on developing more diverse culture.…”
Section: Nine Repertoiresmentioning
confidence: 99%
“…The virtuous circle once again appears: diverse populations need diverse librarians (Bonnet and McAlexander, 2012); diverse librarians need to offer diverse services and programmes (Cruz, 2019), diverse librarians need to be attracted to and developed within visibly culturally competent programmes (Lilley and Paringatai, 2014; Roy, 2017; Villagran and Hawamdeh, 2020; White, 2017) and they need to be taught by diverse faculty, who once were students. The support and commitment of the professional associations as agents of standards evaluation is paramount (Hill, 2021). Specialist groups such as the Association for Library Service to Children (ALSC), whose competences strongly focus on diversity and inclusion (ALSC, 2020), contribute to ‘strengthen the social justice fabric of the profession’ (Moreillon, 2015: 212).…”
Section: Nine Repertoiresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper of Al, Andrade Blanco & Chiranov (2015) 13 Libraries for all projects and the studies brought within the project scope are performed and discussed on the role of libraries as knowledge environments, and they found that local libraries have the potential to be used as knowledge environments. The study of Hill (2021) 14 found that the guidelines provide a perception of inefficiency and convenience in library personnel, library administration, and library support and services issues. While this is not unexpected, the circumstances of the incapacity and other law considerations reflect a shared notion of admission that goes deeper than what the law demands.…”
Section: Literature Reviewmentioning
confidence: 99%